2014
DOI: 10.1093/toxsci/kfu073
|View full text |Cite
|
Sign up to set email alerts
|

PARP-1 Hyperactivation and Reciprocal Elevations in Intracellular Ca2+ During ROS-Induced Nonapoptotic Cell Death

Abstract: The generation of reactive oxygen species (ROS) has been implicated in the pathogenesis of renal ischemia/reperfusion injury, and many other pathological conditions. DNA strand breaks caused by ROS lead to the activation of poly(ADP-ribose)polymerase-1 (PARP-1), the excessive activation of which can result in cell death. We have utilized a model in which 2,3,5-tris(glutathion-S-yl)hydroquinone (TGHQ), a nephrotoxic and nephrocarcinogenic metabolite of hydroquinone, causes ROS-dependent cell death in human rena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 40 publications
3
26
0
Order By: Relevance
“…Accumulating evidence suggests that ROS contributes to DNA damage and PARP-1 hyperactivation, the excess of which, can result in PARP-1-dependent cell death (parthanatos) 11 , 12 . Some studies have demonstrated that calcium was required for the PARP-1 hyperactivation in the model of oxidative stress-induced cell death 28 , 29 . Consistently, in our results, the production of ROS and calcium are increased in MNNG-induced parthanatos.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence suggests that ROS contributes to DNA damage and PARP-1 hyperactivation, the excess of which, can result in PARP-1-dependent cell death (parthanatos) 11 , 12 . Some studies have demonstrated that calcium was required for the PARP-1 hyperactivation in the model of oxidative stress-induced cell death 28 , 29 . Consistently, in our results, the production of ROS and calcium are increased in MNNG-induced parthanatos.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, accumulating evidence suggests that ROS has a critical role in calcium balance. Zhang et al 29 reported that intracellular calcium is required for ROS-induced PARP-1 hyperactivation in non-apoptotic cell death. Furthermore, Robert et al 30 found that mitochondrial ROS is required for elevation of cytosolic calcium.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, following DNA damage, NAD + levels can drop low enough that glycolysis and substrate flux to the mitochondria is blocked leading to cell death, despite having an excess of available glucose (Alano et al, 2010; Benavente et al, 2009; Ying et al, 2005; Zhang et al, 2014). This finding highlights the need to understand the mechanisms interconnecting subcellular NAD + pools, as their homeostasis and interaction is essential for the preservation of cell viability and ATP levels.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, cell death induced by ischemia/reperfusion shares many of the same characteristics: ROS induction, PARP1 hyperactivation, calcium release, AIF translocation, and caspase-independence. 20 , 21 Similarly, treatment with methylnitronitrosoguanidine (MNNG; a DNA alkylating agent) or induction of neuronal excitotoxicty induces PARP1 hyperactivation and cell death, but without futile cycle-induced ROS production. 22 , 23 , 24 Recent studies suggest an important role for accumulated free PAR polymer that can directly activate μ -calpain, activate and release AIF, and inhibit glycolysis.…”
mentioning
confidence: 99%